Multilayer microparticles for programmed sequential release of phenolic compounds from Eugenia stipitata: Stability and bioavailability - Queiroz de Oliveira, Williara (2024)
A co-delivery system based on multilayer microparticles was developed and characterized for the sequential release of phenolic compounds (PCs) using different encapsulation processes (spray drying: SD and drying-chilling spray: SDC) and wall materials to improve the stability and bioavailability of PCs. Samples were characterized in terms of process yield (PY%), phenolic retention efficiency (PRE%), chemical structure and crystallinity (NMR, FTIR, DXR), thermal stability (DSC and FT-IR), anti-radical capacity (ORAC and ABTS) and in vitro digestion. PRE% of samples by SD were higher (p < 0.05) than SDC due to the formation of PCs from CRF (cará-roxo flour). NMR, FTIR, DXR confirmed the presence of key components and interactions for the formation of the advanced co-delivery system. The SDC particles showed crystalline regions by XRD and were stable at ∼47 °C. All samples showed good release of PC in the intestinal phase, and antiradical capacity that reached 23.66 µmol TE g−1.